2020
DOI: 10.1111/bjh.16681
|View full text |Cite
|
Sign up to set email alerts
|

New developments in von Willebrand disease

Abstract: Summary Von Willebrand disease (VWD) constitutes the most common inherited human bleeding disorder. It is associated with a mucocutaneous bleeding phenotype that can significantly impact upon quality of life. Despite its prevalence and associated morbidity, the diagnosis and subclassification of VWD continue to pose significant clinical challenges. This is in part attributable to the fact that plasma von Willebrand factor (VWF) levels vary over a wide range in the normal population, together with the multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 99 publications
(149 reference statements)
0
32
0
15
Order By: Relevance
“…18 In contrast, although it accounts for the majority of VWD cases, the pathobiology underpinning partial quantitative deficiency of VWF, has remained elusive. 13 However, important insights have been gained from several recent cohort studies. 17,[19][20][21][22] These studies have demonstrated that reduced plasma VWF:antigen (VWF:Ag) levels may result from (1) a decrease in VWF biosynthesis within endothelial cells (ECs), (2) a decrease in VWF secretion from EC, or (3) an increase in plasma VWF clearance.…”
Section: Insights Into Quantitative Vwd Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…18 In contrast, although it accounts for the majority of VWD cases, the pathobiology underpinning partial quantitative deficiency of VWF, has remained elusive. 13 However, important insights have been gained from several recent cohort studies. 17,[19][20][21][22] These studies have demonstrated that reduced plasma VWF:antigen (VWF:Ag) levels may result from (1) a decrease in VWF biosynthesis within endothelial cells (ECs), (2) a decrease in VWF secretion from EC, or (3) an increase in plasma VWF clearance.…”
Section: Insights Into Quantitative Vwd Pathogenesismentioning
confidence: 99%
“…Accumulating data over recent years has provided important advances in our understanding of VWD pathobiology. 13,[15][16][17] In particular, it has become clear that several distinct subgroups within partial quantitative VWD can now be defined. In this review, these insights into quantitative VWD pathogenesis will be considered.…”
mentioning
confidence: 99%
“…VWD constitutes the most common inherited bleeding disorder and affects up to 1 in 1000 individuals 2,4 . The majority of VWD is caused by mutations at the VWF gene locus on chromosome 12 5 .…”
Section: Figurementioning
confidence: 99%
“…2,3 VWD constitutes the most common inherited bleeding disorder and affects up to 1 in 1000 individuals. 2,4 The majority of VWD is caused by mutations at the VWF gene locus on chromosome 12. 5 These mutations affect VWF biosynthesis within EC in a variety of different ways, ultimately leading to either quantitative (Type 1 VWD) or qualitative (Types 2A, 2B, 2M, or 2N VWD) VWF deficiencies and a consequent bleeding phenotype.…”
mentioning
confidence: 99%
“…Interestingly, although H antigen is expressed on platelet-derived VWF, there is no A or B antigen expression 13 , 14 . ABO(H) expression on VWF is important because it has been shown to regulate multiple aspects of VWF biology 15 , 16 . First, ABO affects plasma levels of the VWF-FVIII complex, with significantly lower levels in blood group O compared to non-O subjects 17 .…”
Section: Introductionmentioning
confidence: 99%